Improving The Sustainability Of Alen-Alen Household Industry Business In Sumbergedong Village, Trenggalek - Juliani Pdjowati; Sri Tri Wahyumi; Khusnul Khotimah Al Akalili (Nomico, 2025)
This study aims to examine and analyze the improvement of business sustainability for the home industry of alen-alen in Sumbergedong Village, Trenggalek District, Trenggalek Regency. This study uses a qualitative approach. Data collection methods used are interviews, documentation and observation. The research subjects were the owners of the Alen-alen home industry in Sumbergedong Village, Trenggalek District, Trenggalek Regency as informants. The triangulation used is source and method triangulation.The results showed that the home industry of alen-alen in Sumbergedong Village, Trenggalek District, Trenggalek Regency still faces problems in running its business. These problems such as human resources are still lacking, weak business and marketing networks and technological limitations. Efforts made by the home industry of Alen-alen in Sumbergedong Village in improving business sustainability are by optimizing capital, raw materials, marketing, technology and labor.